OVERTIME TRAP: LITERATURE REVIEW BURNOUT MECHANISM AND DECLINING WORK–LIFE BALANCE - Rusidari; Agung Surya Dwianto (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Overtime has become a strong feature of modern work culture, especially in high-pressure sectors in Asia, such as manufacturing, logistics, and services. Although many studies have proven the link between long working hours and the deterioration of employee welfare, the mechanisms explaining how overtime causes an imbalance between work and personal life (Work-life Balance) have not yet been fully explored and pieced together. This narrative literature review aims to synthesize findings from key and recent studies published between 2000 and 2025. The goal is to form a conceptual framework of understanding how overtime can trigger burnout (emotional, mental, and physical exhaustion) and ultimately disrupt WLB. Based on four main theoretical foundations, namely Job Demands–Resources (JD-R), Conservation of Resources (COR), Effort Recovery Model, and Work–Home Resources Model, this review identifies three main pathway mechanisms: (1) Overtime increases job demands while simultaneously reducing opportunities for self-recovery. (2) Burnout, especially emotional exhaustion, acts as a psychological strain that mediates the effects of overtime. (3) The spillover effects of burnout trigger interference between work and home domain through time based conflicts and strain. Organizational support, job autonomy, family roles, marital status, gender and workload pressure are important moderators that can strengthen or weaken the relationship between each variable. While the theoretical contribution of this review lies in combining various perspectives into a conceptual model of the "overtime trap," its practical contribution lies in proposing implications for organizations, job redesign, fatigue management, and more adaptive work policies. Future research is expected to use longitudinal, mixed-method, and cross-cultural designs to validate, strengthen and expand this model.